Comparing dead reckoning algorithms for distributed car simulations - Chen, Youfu (2019)
Dead reckoning is an important technique used in distributed virtual environments (DVEs) to mitigate the bandwidth consumption of frequent state updates and the negative effects of network latency. This paper proposes a novel dead reckoning approach for common DVE applications such as multiplayer online games. Unlike traditional dead reckoning approaches that estimate the movements of remote entities with pure kinematic models, the new approach performs extrapolations with the considerations of environmental factors and human behaviours. We have performed experiments, based on a distributed car simulator, to compare the the new approach with representative existing dead reckoning approaches. The results show that the new approach gives more accurate predictions with an acceptable overhead.